Baseline data for Farm level and community aggregate economic impacts of adopting Climate Smart Agricultural Practices in three Mega Environments - Le, Lan; Sain, Gustavo; Czaplicki, Stanislaw; Guerten, Nora; Shikuku, Kelvin Mashisia; Grosjean, Godefroy; Läderach, Peter R.D. (International Center for Tropical Agriculture, 2019)
The data includes baseline surveys of 170 farmers in Vietnam, 180 farmers in Nicaragua and 1330 farmers in Uganda. Survey questions covered a wide range of topics ranging from demographic, socio-economic data, social capital, land use and land tenure; perception of current and future climate risks and associated impact; labors and crops production activities. Cost and benefits of CSA practices were also collected from the household surveys